The Effect of Activity-Based Costing on Profitability with Management Information Quality as a Moderating Variable - Salsabilah Catur Sakinah; Rahmad Hidayat; Mukhtaruddin Mukhtaruddin (Dinasti Publisher, 2025)
This research aims to provide an understanding of Activity-Based Costing (ABC) and its implications for profitability, with the quality of management information as a moderating variable. This study uses a Systematic Literature Review (SLR) approach to articles indexed by Scopus Q1–Q4 and Sinta 2–Sinta 5 in the period 2010–2025. The results of the study show that the results of the Systematic Literature Review of 76 articles show that Activity-Based Costing (ABC) has a positive and significant effect on company profitability. This system increases the accuracy of cost information, operational efficiency and more competitive pricing strategies, thereby strengthening financial performance such as NPM, ROA and ROE. Quality Management Information (KIM) is proven to strengthen the relationship between Activity-Based Costing (ABC) and profitability by increasing the reliability and understandability of cost data. When the quality of information is high, the results of Activity-Based Costing (ABC) are more effectively used for strategic decision making, efficiency and increasing company value.